Facile preparation of a metal-phenolic network-based lymph node targeting nanovaccine for antitumor immunotherapy. (1st March 2023) - Su, Qianhong; Liu, Zuwei; Du, Ruolin; Chen, Xiaolu; Chen, Longlong; Fu, Zhaoming; Luo, Xingyu; Yang, Yong; Shi, Xuequn
Abstract: Cancer vaccines are being explored for enhanced cancer immunotherapy and prophylaxis. Some of their prevailing weaknesses, however, such as complicated preparation, poor biocompatibility, and failure to elicit strong cellular immune responses, have limited their further clinical applications. Here, we reported a multifunctional nanovaccine that was prepared in a quick and simple way. During the self-assembly of metal-phenolic networks (MPNs), the antigen ovalbumin (OVA) and immunoreactive chlorogenic acid (CHA) were simultaneously loaded. Owing to its dual pH and reduction sensitivities, the nanovaccine could deliver antigens into the cytoplasm of dendritic cells (DCs) and facilitate the cross-presentation of antigens. Moreover, the results of in vivo immunization assays demonstrated that the nanovaccine significantly excited the antigen presentation of DCs and provoked a robust cellular immune response with the restrained activation of regulatory T cells (Tregs), by targeting lymph nodes and executing the function of CHA. In vivo antitumor assays indicated that the nanovaccine with good biocompatibility afforded conspicuous cancer treatment and prevention effects. Overall, the nanovaccine presented in this study shows a promise for potentiating cancer immunotherapy by the lymph node-targeted delivery. Statement of significance: Cancer nanovaccines can be used for cancer immunotherapy. However, some existing shortcomings, such as cumbersome preparation, poor biocompatibility, and failure to elicit strong immune responses, limit the clinical application of cancer nanovaccines. This study developed a multifunctional nanovaccine that was readily prepared through the self-assembly of metal-phenolic networks. The nanovaccine with dual pH and reduction sensitivities could efficiently promote the antigen lysosome escape and cross-presentation. In vivo, it efficiently delivered antigen into lymph nodes and provoked strong cellular immune responses, and thus it showed significant cancer immunotherapy and prevention effect. Graphical abstract: Image, graphical abstract